Association between morphophysiological and functional characteristics with activities of daily living in elderly women participating in community programs in the city of Critiba, PR - Maressa Priscila Krause (Universidade Federal de Santa Catarina, 2007)
Objective: to examine the association between the performance of Activities of Daily Living (ADLs) and level of physical activity, physical and functional fi tness in elderly women. Methods: The sample was composed of 1,069 women, (≥60 years). Socioeconomic status, physical activity level, and activities of daily living were determined by questionnaires, while physical and functional fi tness were assessed through body composition, cardiorespiratory assessment and motor ability. Descriptive values, ANOVA one way, Tukey post hoc, Pearson correlation, and logistic regression analysis (p<0.05) were employed. Results: According to the anthropometric analysis it was verifi ed that older women exhibited lower body adiposity, mainly in the upper body, when compared with women at a younger age group. The younger women exhibited a higher level of physical activity, in the total, domestic and sport categories, when compared with older women. A similar relationship was observed in the performance of all physical and functional fi tness variables. Furthermore, when comparing dependence and loss of independence by age (from younger to older women) it was perceived that dependence increased with age. This relationship was confi rmed through logistic regression analysis, where age was demonstrated of being predictive of dependence or the loss of independence (p=0.016 and, p<0.001, respectively), indicating that aging increases women's risk of losing their independence. Multivariate analysis demonstrated that exercise/physical activity level was a strong predictor for ADLs (lower group OR 1.91 CI 95% 1.17-3.12; p=0.009, when compared with the upper group). In the multivariate analysis, level of physical activity (lower group OR = 2.96; CI 95% 2.04-4.29; p<0.001 and medium group 2 OR = 1.86; CI 95% 1.30-2.65; p=0.001, when compared with the upper group), and maximum upper body strength (lower group OR = 1.91; CI 95% 1.21-2.99; p<0.005, when compared with the upper group) were predictors of IADLs. Conclusion: The aging process, undoubtedly, causes a decrease in independence, and this being so, it is expected that subjects suffer a decrease of their physical and functional capacities. The maintenance of an elevated level of physical activity, but mainly regular exercise could sustain independence for a longer period of time. It is suggested that public health initiatives be planned with the objective of maintaining health, independent living, and consequently a satisfactory quality of life for the elderly. Therefore, it can be suggested that intervention programs that promote regular physical activity with careful planning and control should be offered for this population. RESUMO Objetivo: examinar a associação do nível de atividade física e as variáveis da aptidão física e funcional com a performance das Atividades da Vida Diária (AVDs), em mulheres idosas. Metodologia: A amostra foi constituída por 1.069 mulheres (≥60 anos). O nível sócio-econômico, nível de atividade física, e atividades da vida diária foram determinados através de questionários, enquanto que a aptidão física e funcional foi avaliada através da composição corporal, aptidão cardio-respiratória e neuro-muscular. Foram utilizados valores descritivos, ANOVA one way, post hoc Tukey, correlação de Pearson e, análise de regressão logística (p<0,05). Resultados: A partir da análise antropométrica verifi cou-se que as mulheres mais velhas apresentam menor adiposidade corporal, principalmente na região superior do corpo, quando comparada às mulheres pertencentes à faixa etária mais jovem. As mulheres mais jovens apresentaram maior nível de atividade física, nas categorias total, doméstica e esportiva, quando comparadas às mais idosas. Relação similar pôde ser observada na performance de todas as variáveis da aptidão física e funcional. Além disso, ao comparar a dependência e a perda da independência entre as faixas etárias (mais jovens para as mais idosas) percebeu-se que ocorreu um aumento da dependência. Essa relação é confi rmada através da análise de regressão logística, onde a idade demonstrou ser preditora da dependência ou da perda da independência (p=0,016 e, p<0,001, respectivamente). A análise multivariada, demonstrou que o nível de atividade física esportivo foi um forte preditor das AVDs (grupo inferior OR 1,91 IC95% 1,17-3,12; p=0,009). Enquanto que o nível de atividade física (grupo inferior OR = 2,96; IC 95% 2,04-4,29; p<0,001 e grupo médio OR = 1,86; IC95% 1,30-2,65; p=0,001) e a força máxima de membros superiores (grupo inferior OR = 1,91; IC 95% 1,21-2,99; p<0,005) foram preditores das AIVDs. Conclusão: O avanço da idade, indiscutivelmente, ocasiona uma diminuição da independência, sendo assim, é esperado que os indivíduos reduzam suas capacidades físicas e funcionais. A manutenção do nível de atividade física, principalmente da prática regular de exercícios físicos pode sustentar a independência por um período de tempo mais longo. Sendo assim, sugere-se que as iniciativas de saúde pública sejam planejadas com o objetivo de manutenção da saúde, da vida independente, e consequentemente de uma satisfatória qualidade de vida aos idosos. Para tal, aconselha-se programas de intervenção que promovam exercícios físicos regulares, com o devido planejamento e controle, para esta população.